Flexing sebagai Strategi Representasi Diri di Media Sosial: Studi Fenomenologis pada Mahasiswa Ilmu Komunikasi Universitas Malikussaleh - Syarifah Chairunnisak; Sayed Ludhfi; Depita Kardiati; Fitria Akmal; Yuli Santri Isma; Jamiati KN; Sarrah Kurnia Fadhillah (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of flexing on social media is increasingly developing as a form of self-image, especially among students. Flexing is a behavior that displays certain achievements, wealth, or lifestyles with the aim of gaining social validation. This study aims to explore the subjective meaning of the flexing phenomenon on social media and its impact on the digital identity and social relations of Communication Science students at Malikussaleh University. Using a qualitative approach and phenomenological method, this study serves the experiences and meanings of students purposively from Communication Science students of the 2022 intake who actively use social media. The data collection technique was carried out through in-depth interviews, which were then analyzed thematically. The results of the study showed that students interpreted flexing as part of personal branding but also as a form of social pressure. Flexing can increase self-confidence and motivation, but also cause anxiety and feelings of insecurity due to social comparison. In the context of social interaction, flexing has ambivalent impacts, such as expanding social networks but can also create social distance. This study emphasizes the importance of digital literacy and reflective awareness in using social media in a healthy way.